The Indirect Effect of Trauma via Cognitive Biases and Self-Disturbances on Psychotic-Like Experiences - Pionke-Ubych, Renata; Frydecka, Dorota; Cechnicki, Andrzej; Nelson, Barnaby; Gawęda, Łukasz (Frontiers in Psychiatry, 2021)
Although self-disturbances (SD) are considered to be a core psychopathological feature of schizophrenia spectrum disorders, there is still insufficient empirical data on the mechanisms underlying these anomalous self-experiences. The aim of the present study was to test a hypothesized model in which cognitive biases and exposure to traumatic life events are related to the frequency of SD which, in turn, contribute to the frequency of psychotic-like experiences (PLEs). Our sample consisted of 193 Polish young adults from the general population (111 females; 18 – 35 years of age, M = 25.36, SD = 4.69) who experience frequent PLEs. Participants were interviewed for PLEs, SD and social functioning as well as completed self-reported questionnaires and behavioral tasks that measure cognitive biases (e.g. safety behaviours, attention to threat, external attribution, jumping to conclusion, source monitoring, overperceptualization). The model was tested using path analysis with structural equation modeling. All of the hypothesized relationships were statistically significant and our model fit the data well (χ2(23) = 31.201; p = 0.118; RMSEA = 0.043 [90% CI = 0.00 – 0.078], CFI = 0.985, SRMR = 0.041, TLI = 0.976). The results revealed a significant indirect effect of traumatic life events on PLEs through SD and self-reported cognitive biases. However, performance-based cognitive biases measured with three behavioral tasks were unrelated to SD and PLEs. The frequency of SD explained a substantial part (43.1%) of the variance in PLEs. Further studies with longitudinal designs and clinical samples are required to verify the predictive value of the model.